The Berenstain bears' new baby - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random House, 1974)
Small Bear outgrows the bed his father made him when he was a baby--and none too soon.
Accelerated Reader
Keywords: Brothers and sisters -- Fiction